Influencing variables and scenarios for the frozen fruit agro-export sector: the peruvian case - Alvarez Gallegos, Ariana Mariell (2023)
In recent years, the agro-export sector in Peru has undergone constant changes caused by the political context, technological advances, among others, which affect the market share of Peruvian producers compared to other countries producers in this sector. This research focuses on identifying the most influential variables to determine future scenarios in the Peruvian agro-export sector of frozen fruits. The study analyses mango, blueberry and strawberry exports in Peru, in order to promote the development and growth of this sector. It has a mixed approach and follows Godet's prospective strategy as a research methodology. To this end, interviews were conducted with experts to find the most influential variables and factors were identified for the analysis of key variables using the Multiplicative Cross Impact Matrix Applied to a Classification (MICMAC) method and the construction of scenarios using the System of Cross Impact Matrices (SMIC) method. The conclusions of the study indicate that the variables with the greatest impact are exogenous, such as the implementation of agricultural technologies and adequate cold chain logistics. These results allow us to propose possible scenarios that can be used to develop improvement proposals for the future development of the sector.